Antigen‐specific airway IL‐33 production depends on FcγR‐mediated incorporation of the antigen by alveolar macrophages in sensitized mice. Issue 1 (19th April 2018) - Nabe, Takeshi; Matsuda, Masaya; Ishida, Tomoki; Tsujimoto, Nau; Kido, Hitomi; Kanaya, Haruna; Takahashi, Hiromu; Takemoto, Naoki; Nomura, Miku; Ishihara, Keiichi; Akiba, Satoshi; Mizutani, Nobuaki
Summary: Although interleukin (IL)‐33 is a candidate for the aggravation of asthma, the mechanisms underlying antigen‐specific IL‐33 production in the lung are unclear. Therefore, we analysed the mechanisms in mice. Intra‐tracheal administration of ovalbumin (OVA) evoked increases in IL‐33 and IL‐33 mRNA in the lungs of both non‐sensitized and OVA‐sensitized mice, and the increases in the sensitized mice were significantly higher than in the non‐sensitized mice. However, intra‐tracheal administration of bovine serum albumin did not increase the IL‐33 level in the OVA‐sensitized mice. Depletion of neither mast cells/basophils nor CD4 + cells abolished the OVA‐induced IL‐33 production in sensitized mice, suggesting that the antigen recognition leading to the IL‐33 production was not related with either antigen‐specific IgE‐bearing mast cells/basophils or memory CD4 + Th2 cells. When a fluorogenic substrate‐labelled OVA (DQ‐OVA) was intra‐tracheally administered, the lung cells of sensitized mice incorporated more DQ‐OVA than those of non‐sensitized mice. The lung cells incorporating DQ‐OVA included B‐cells and alveolar macrophages. The allergic IL‐33 production was significantly reduced by treatment with anti‐Fc γ RII/III mAb. Depletion of alveolar macrophages by clodronate liposomes significantly suppressed the allergic IL‐33 production, whereas depletion of B‐cells by anti‐CD20 mAb did not. These results suggest that the administered OVA in the lung bound antigen‐specific IgG Ab, and then alveolar macrophages incorporated the immune complex through Fc γ RII/III on the cell surface, resulting in IL‐33 production in sensitized mice. The mechanisms underlying the antigen‐specific IL‐33 production may aid in development of new pharmacotherapies. Abstract : Although interleukin (IL)‐33 is a candidate for the aggravation of asthma, the mechanisms underlying antigen‐specific IL‐33 production in the lung are unclear. Antigen‐specific IL‐33 production in the lung of sensitized mice was not dependent on either mast cells or Th2 cells, but on FcγR‐mediated incorporation of the antigen by alveolar macrophages. The mechanism underlying the antigen‐specific IL‐33 production may aid in development of new pharmacotherapies.